Democratic Innovation and Participation as Part of the New Public Management: A Critical Review of Gender Mainstreaming in the Kenyan Legislature - Muthama, Johnson Nduya (European Journal of Applied Sciences, 2025)
There has been a proliferation of democratic innovations aimed at improving democratic systems within a particular social, political and economic environment. This study aimed to evaluate the extent to which an innovative democratic approach, namely gender equity and equality, has been mainstreamed as part of democratic participation in the new public management in the Kenyan legislature. The study applied three complementary theories, that is, (1) the democratic innovation theory (Asenbaum, 2021; Cunningham, 2002; Elstub et al., 2016; Elstub & Escobar, 2019; Fung, 2015; Smith, 2005; 2009; 2019); and (2) changing organisational culture (Cameron & Quinn, 2006); both leading to (3) competing values in public administration (Hood, 1991). Findings revealed that there were certain achievements, just as there were challenges, in order to achieve the stipulations of the gender rule in a social-cultural and political context. This is because despite its legal basis, a democratic innovation may lack a basis in social-cultural settings and thus by itself, in law or out of law, it does not, and may not, automatically lead to democratic participation. Instead, it is imperative that the social context and both the more informal and formal principal laws operate side by side to promote participatory democracy, rather than a fixation on democratic innovation.